Advanced oxidation technologies to remove endocrine disruptors in water effluents based on zinc supported mesoporous catalysts - Carraro, Paola María (2018)
Mesoporous silica material type MCM-41 was modified with different amounts of Zn (1-15 wt.%) by the wet impregnation method. Support and catalysts were characterized by means of powder X-ray diffraction (XRD), N2 nitrogen adsorptiondesorption, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and ICP-OES techniques. The Zn-modified mesoporous silicates have been successfully tested for the degradation in aqueous solutions of different endocrinedisrupting (EDs), such as herbicides (atrazine), compounds derived from the plastic industry (bisphenol A) and from the pharmaceutical industry (clofibric acid). The results showed that the Zn/M(5) catalyst exhibited the highest activity. The high performance of this material indicates that the heterogeneous photo-Fenton-like reaction appears as a very promising pretreatment capable of enhancing the biodegradability of water contaminated with biorecalcitrant chemicals, as the most endocrine disruptors.